Lipidomics reveals the dynamics of lipid profile altered by omega‐3 polyunsaturated fatty acid supplementation in healthy people. (11th March 2020) - Yan, Meng; Cai, Wen‐Bin; Hua, Tong; Cheng, Qian; Ai, Ding; Jiang, Hong‐Feng; Zhang, Xu
Abstract: Glycerophospholipids (GPs) and sphingolipids (SPs) are important lipid components in the body and play biological functions. Omega‐3 polyunsaturated fatty acids (n‐3 PUFAs) are important nutrients, and their supplements are commonly used for preventing some diseases. However, the effect of n‐3 PUFAs on the human glycerophospholipidome and sphingolipidome is unclear. We used targeted lipidomics to study the GP and SP profile of healthy individuals after supplementation with n‐3 PUFAs for 3, 7, 14 and 21 days. Fuzzy c‐means clustering was used to cluster the lipid species into six classes reflecting different changed‐content patterns after n‐3 PUFA supplementation. Among the species with significantly changed content, lysophospholipids were the most sensitive; their content started to increase on day 3. The content of phosphatidylserines increased at a later stage. The content of most of the phosphatidylcholines and alkylphosphatidylcholines decreased on day 21. A correlation network analysis of lipid species suggested that some enzymes involved in the metabolism of lysophospholipids and phosphatidylserines were regulated by n‐3 PUFAs. Levels of creatine kinase‐MB (CK‐MB), urea, glucose, triglycerides and total bilirubin were altered by n‐3 PUFA at 21 days. Correlation analysis revealed that the level of CK‐MB was negatively correlated with those of species in lysophosphatidic acid, lysophosphatidylcholine, lysophosphatidylethanolamine and phosphatidylserine classes, which were increased by n‐3 PUFA supplementation. With the analysis in this work, we demonstrated the regular pattern of n‐3 PUFAs on GP and SP metabolism, which provides a pharmacological basis for n‐3 PUFAs for clinical application.